After Carson: reading as anacoluthon. Issue 5 (28th July 2016) - Entwistle, Alice; Mills, Kevin
ABSTRACT: Ciaran Carson's writing plays with and renders strange all kinds of literary and generic classifications. The subject of numerous short critical accounts, a monograph and at least one collection of essays, his work, especially the poetry, has attracted a good deal of scholarly attention. 'After Carson' offers a hybridic, 'creative-critical' response to a genre-busting idiom. Focussing on just two of Carson's works, the well-known and much-discussed Belfast Confetti (1989), and the complex but less carefully read prose work The Star Factory (1997), the formal self-consciousness of this treatment is intended to problematise the conceptual and textual bounds of conventional literary scholarship. The intention is to figure, as well as justify, the disruption of conventional linear argument with the help of the subversive energies to be discovered in collision, lapse, detour, ambush, and / or other kinds of discursive misconduct. Informed partly by dissatisfaction with most theories of reading, our critique is particularly interested in how three different kinds of reading can be shown to complicate both their subject and each other. Firstly, it casts the reader's relationship with Carson in the paradoxical, counter-conclusive terms of 'anacoluthon': a rhetorical figure of errant predication (a following which does not follow). Secondly it argues that Carson's work reflexively interrogates the will to distinguish between creative and critical modes, rendering any act of interpretation productively unstable. Finally, in its co-authorship, the account knowingly doubles – at once destabilising and deferring – the authorising singularity of the critical voice, suspending a habitually hegemonic 'I' between our differently contextualised, differently gendered signatures.